ANALISIS KARAKTERISTIK GAYA BELAJAR MAHASISWA PENDIDIKAN BAHASA INGGRIS ANGKATAN 2016 STKIP BINA BANGSA GETSEMPENA BANDA ACE - Syarfuni; Verawati (Jurnal Genta Mulia, 2017)
One of the characteristics of learning is related to absorbing, processing and conveying This information is the student's learning style. Learning style is a very learning modality important. Information related to the characteristics of the learning styles of the students who will be taught is very important for lecturers to improve the quality of learning. Students will also find it easier to motivate themselves learning. This research is a qualitative descriptive study. The subjects of this research are all English language education study program students class of 2016. Instruments used in This research is in the form of a questionnaire which will be filled out by research subjects. This learning style questionnaire is filled out by 42 research subjects. The results of the learning style analysis are dominated by combined learning styles auditory and kinesthetic 25% Visual 12%, 20% auditory, 24% kinesthetic, 7% combined visual and auditory, 12% combined visual and kinesthetic. Thus, the dominance of student learning style tendencies are auditory and kinesthetic learning styles.